2015
DOI: 10.3168/jds.2014-8564
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced early-life nutrition promotes hormone production and reproductive development in Holstein bulls

Abstract: Holstein bull calves often reach artificial insemination centers in suboptimal body condition. Early-life nutrition is reported to increase reproductive performance in beef bulls. The objective was to determine whether early-life nutrition in Holstein bulls had effects similar to those reported in beef bulls. Twenty-six Holstein bull calves were randomly allocated into 3 groups at approximately 1 wk of age to receive a low-, medium-, or high-nutrition diet, based on levels of energy and protein, from 2 to 31 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
54
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 31 publications
11
54
2
5
Order By: Relevance
“…In a similar study performed recently on Holstein-Friesian and Jersey bull calves between 3 to 49 weeks of age these results could be confirmed (Byrne et al, 2017). In addition, Dance et al (2015) noticed at 72 weeks, that bulls fed the highnutrition diet had greater paired testes weights. The estimated number of sperm produced by day in the bulls of the high-nutrition group was about 9% higher compared to the bulls of medium-nutrition group and about 30% higher than the number estimated in bulls of the low-nutrition group, while no differences in sperm quality were noticed depending on nutrition of the bulls (Dance et al, 2016).…”
Section: Effects Of Modifications In Nutrition Starting During the Insupporting
confidence: 71%
See 3 more Smart Citations
“…In a similar study performed recently on Holstein-Friesian and Jersey bull calves between 3 to 49 weeks of age these results could be confirmed (Byrne et al, 2017). In addition, Dance et al (2015) noticed at 72 weeks, that bulls fed the highnutrition diet had greater paired testes weights. The estimated number of sperm produced by day in the bulls of the high-nutrition group was about 9% higher compared to the bulls of medium-nutrition group and about 30% higher than the number estimated in bulls of the low-nutrition group, while no differences in sperm quality were noticed depending on nutrition of the bulls (Dance et al, 2016).…”
Section: Effects Of Modifications In Nutrition Starting During the Insupporting
confidence: 71%
“…The estimated number of sperm produced by day in the bulls of the high-nutrition group was about 9% higher compared to the bulls of medium-nutrition group and about 30% higher than the number estimated in bulls of the low-nutrition group, while no differences in sperm quality were noticed depending on nutrition of the bulls (Dance et al, 2016). Overall, the results obtained by Dance et al (2015Dance et al ( , 2016 and Byrne et al (2017) are consistent with the studies from Brito et al (2007a, c, d), who modified the nutrition of beef bulls starting at the prepubertal period. All these studies provide clear evidence that nutritional modulation of bull calves before puberty has profound effects on reproductive development.…”
Section: Effects Of Modifications In Nutrition Starting During the Insupporting
confidence: 70%
See 2 more Smart Citations
“…Other authors concluded that daily gains of greater than 1.2 kg/day during calf-hood should be targeted to ensure earlier attainment of puberty in bulls [9]. More recently, a higher plane of nutrition led to a greater scrotal circumference (SC) and thus hastened age at puberty in Holstein-Friesian bulls [10]. It has also been suggested that SC can be used as a predictor of sperm output potential in young dairy bulls [11].…”
Section: Introductionmentioning
confidence: 99%